Analysis Proximate of Nerita costata and Nerita maxima Collected from Hutumuri and Latuhalat Beaches in Ambon, Maluku, Indonesia - Rafdin, Rafdin; Liline, Sintje; Salmanu, Sriyanti Imelda Aksamina (Universitas Pattimura, 2026)
Nerita sp. is a type of gastropod that is commonly consumed by the people of Ambon Island, especially in the villages of Hutumuri and Latuhalat, and has the potential to be an alternative food source. However, its nutritional content has not been studied in detail. This research aims to analyze the proximate content, including moisture, ash, protein, fat, carbohydrates, and fiber, in Nerita maxima and Nerita costata from both locations. The study used a descriptive approach with random sampling techniques from the waters of Hutumuri Beach and Latuhalat Beach. Proximate analysis was conducted in the laboratory using the standard AOAC (Association of Official Analytical Chemists) methods.The analysis results show that at Hutumuri Beach, Nerita costata has a moisture content of 79.24%, ash 1.18%, protein 12.80%, fat 1.79%, carbohydrates 2.16%, and fiber 0.18%. Meanwhile, Nerita maxima has a moisture content of 81.30%, ash 1.10%, protein 13.90%, fat 1.72%, carbohydrates 1.66%, and fiber 0.19%. At Latuhalat Beach, Nerita costata has a moisture content of 76.80%, ash 1.48%, protein 17.02%, fat 2.75%, carbohydrates 1.49%, and fiber 0.20%. Whereas, Nerita maxima has a moisture content of 78.31%, ash 1.44%, protein 15.47%, fat 2.90%, carbohydrates 1.51%, and fiber 0.23%This research shows that Nerita costata and Nerita maxima from the waters of Latuhalat have higher protein and fat content compared to those from Hutumuri. This indicates that the more fertile and rocky water environment of Latuhalat supports better nutritional value, making these two species potential alternative food sources for the community.